Change Detection Study Of Al Razaza Lake Region Utilizing RemoteSensing And GIS Technique - Ghazal, Nawal; Shaban, Auday; Mashi, Fouad; Raihan, Abdulhadi (Iraqi Journal of Science, 2024)
Remote sensing techniques are now widely used for environment studies, surveysand monitoring. It became a need to study Razaza lake and the surrounding areasespecially when the Antiquities Authority of the Ministry of Tourism announced,that the discovery of the effects under the waters of Lake Razzaza in Karbalaprovince. The aim procedures carried out in this study, the first classified the studyarea by using unsupervised classification method to produce the land cover and landuse ,deriving the elevations as a vector layer using TIN for the whole surroundingregion of lake, the second part, the output is a continuous surface to be created byapplying Kriging interpolation, the third step, obtaining maps of contour lines alsoused to show lines of constant density or brightness by implementations the contourlines , converting the result of interpolation method to a vector values that can becalculated, then the implementation of the classified process and calculating the areaaround the lake, all these steps are done by using ArcGIS. Finally a classificationprocess for the same scene on a different date is applied and then compare it withthe first scene using ERDAS.